Selection of Cashmere Fineness Functional Genes by Translatomics - Zhang, Yu; Zhang, Dongyun; Xu, Yanan; Qin, Yuting; Gu, Ming; Cai, Weidong; Bai, Zhixian; Zhang, Xinjiang; Chen, Rui; Sun, Yingang; Wu, Yanzhi; Wang, Zeying (Frontiers in Genetics, 2022)
Cashmere fineness is an important index to evaluate cashmere quality. Liaoning Cashmere Goat (LCG) has a large cashmere production and long cashmere fiber, but its fineness needs to be improved. Therefore, it is the key to find genes to change cashmere fineness. With the continuous advancement of research, the regulation of cashmere fineness has made new development through high-throughput sequencing and genome-wide association analysis. It has been found that translatomics can identify genes associated with phenotypic traits. From the perspective of translatomics, the skin tissue of LCG was sequenced by Ribo-seq. There were 529 differentially expressed genes among the 27197 co-expressed genes, including 343 up-regulated genes and 186 down-regulated genes. In the GO analysis, there were 491 significantly enriched genes，in the results of KEGG enrichment, cell adhesion molecule pathway, phagosome pathway and leukocyte transendothelial migration pathway had the highest concentration. We found that COL6A5 gene may affect cashmere fineness. The characteristics and expression analysis of COL6A5 gene will make a great contribution to the study of LCG cashmere fineness.